2D distribution of hydrogen/impurity radiation and flow formation in stochastic layer during detachment transition in LHD. (August 2017) - Kobayashi, M.; Morita, S.; Goto, M.; ,
Abstract: 2D distribution of hydrogen/impurity radiation and impurity flow have been measured in the edge stochastic layer of LHD during detachment transition by using a newly developed visible spectrometer system with 130 channel optic fiber array. The spectrometer system views the edge region to resolve magnetic field structures, such as the divertor legs, the X-point, the stochastic layer, the last closed flux surface (LCFS), and the divertor plates. A clear upstream shift of CII and CIII emission from the divertor region to the X-point is observed at the detachment transition. The formation of volume recombination region is indicated by the increase in the ratio Hγ /Hβ, which is particularly enhanced around the LCFS. The flow speed distribution of C 2+ is estimated from the Doppler shift of CIII spectra. The velocity of the order of 10 4  m/s is obtained. A clear change of flow direction is observed with respect to the X-point and the density increase, and at the detachment transition.